The Concept Map of Independent Learning to Prepare the Golden Generation 2045 - Siti Nabilah (Jurnal Manajemen Pendidikan, 2024)
Background The concept of independent learning is an effort to create a learning environment that is free of expression and free from various pressures, but a fun learning activity. Purpose The purpose of this research is to describe the concept map of independent learning to prepare the golden generation 2045. Design/method/approach The method of research is qualitative with literature study techniques. The technique of collecting data is by conducting study studies of books, journals, and articles that are related to the research topic. Results This concept has four aspects that can be used as a basis for preparing this generation. First, the use of technology will make students more critical, active, capable, collaborative, and innovative. Second, the competence of students is needed at the moment. With that competence they have experience, knowledge, they can work faster, problem-solving, and they can also adapt very well. Third, the creativity of students will make them more productive, think smart, good work in team, and they can fast adapt to changes. And fourth, with character education, the students become more respectful, learn to be curious, communicative, responsible, and care for the environment. Contribution/value The concept enhances students' critical thinking, active participation, collaboration, and innovation through technology, enabling them to solve problems efficiently and adapt quickly to changes.